2019
DOI: 10.1055/s-0037-1611765
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of 5-(Trifluoromethyl)[1,2,4]triazolo[1,5-a]pyrimidines from β-Enamino Diketones

Abstract: The use of β-enamino diketones as an easy entry to the regioselective synthesis of [1,2,4]triazolo[1,5-a]pyrimidines is reported. These ketones reacted with 3-amino-1H-1,2,4-triazoles to furnish exclusively 6-substituted 5-(trifluoromethyl)[1,2,4]triazolo[1,5-a]pyrimidines in yields of up to 95%. The regioselectivity of the reactions performed was maintained regardless of the substituent in the starting ketone or aminoazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…On the other hand, in the α‐position, the aroyl group is outside the carbon–carbon double bond plane, meaning that the carbonyl cannot conjugate with the rest of the molecule. [ 67 ] These results indicate the selectivity (reaction occurs only in the planar part of the molecule) and reactivity (reaction occurs only at the most electrophilic centers). For comparison purposes, it was shown that trifluoroacetylated enol ethers bearing a methyl substituent at the α‐position require a greater amount of energy to reach planarity than their β‐substituted parent compound, which indicates that an α‐substituent decreases the reactivity of these conjugated systems in cyclocondensation reactions.…”
Section: Synthesis Of Pyrimidinesmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in the α‐position, the aroyl group is outside the carbon–carbon double bond plane, meaning that the carbonyl cannot conjugate with the rest of the molecule. [ 67 ] These results indicate the selectivity (reaction occurs only in the planar part of the molecule) and reactivity (reaction occurs only at the most electrophilic centers). For comparison purposes, it was shown that trifluoroacetylated enol ethers bearing a methyl substituent at the α‐position require a greater amount of energy to reach planarity than their β‐substituted parent compound, which indicates that an α‐substituent decreases the reactivity of these conjugated systems in cyclocondensation reactions.…”
Section: Synthesis Of Pyrimidinesmentioning
confidence: 98%
“…The first successful selective assembly of the pyrimidine core using unsymmetrical trifluoromethyl β‐enamino diketones 3 was published in 2019 (Scheme 20). [ 67 ] The reaction was done using 3‐amino‐1 H ‐1,2,4‐triazoles in refluxing MeCN for 24 h, which furnished 6‐aroyl‐5‐(trifluoromethyl)[1,2,4]triazolo[1,5‐ a ]pyrimidines exclusively, at moderate to excellent yields (68–95 %). It is important to note that the regioselectivity was maintained, regardless of the substituent in the starting 3 or in the aminoazole.…”
Section: Synthesis Of Pyrimidinesmentioning
confidence: 99%
“…[ 18 ] To overcome the selectivity issue, β‐enamino diketones (see Scheme 1) have emerged as suitable starting materials for the synthesis of several heterocyclic scaffolds, due to presenting high selectivity in most of the cyclocondensation reactions performed. [ 19–21 ] Even though the chemistry of carboxyethyl β‐enamino diketones 1 has been explored, [ 22–29 ] trifluoromethyl 2 ones have been far less used in heterocyclic synthesis. [ 21,30–34 ] Thus, this work aims to study the cyclocondensation reaction between β‐enamino diketones ( CCC building blocks) and 2‐aminobenzimidazole ( NCN ‐dinucleophile), observing the regioselectivity of the obtained products.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Trifluoromethylenamino diketones 1 (Scheme 1), which are prepared from the C-acylation reaction of -dimethylamino ketones ( -enaminones) with trifluoroacetic anhydride, are promising building blocks for type [3+2] or [3+3] cyclocondensation reactions, given that they are highly functionalized structures composed of three electrophilic centers that can furnish three different heterocyclic scaffolds, for cyclocondensation reactions with NCN-dinucleophiles for example (see Scheme 1). [16,17] Despite the possibility of furnishing three different products, the reaction proceeds selectively at site 1 when using NCN-dinucleophiles (guanidine [18,19] and 3-amino-1H-1,2,4-triazole [20] ); how-both products with high regioselectivity (only N 3 -substituted isomer was observed) and high chemoselectivity. A new feature provided by the starting material proposed herein is the possibility to either maintain or eliminate the trifluoromethyl group, by choosing the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…ever, a NN-dinucleophile (hydrazine) provides a mixture of products from sites 1 and 2, as well as a mixture of their isomers. [21] These 1,3-diketones 1 have been shown to be suitable starting materials for preparing several nitrogenated heterocycles such as pyrazoles, [22,23] isoxazoles, [24] triazolopyrimidines, [20] and other aza-heterocycles. [25] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%